The role of employer branding and internal marketing in talent attraction and retention: an applied study in a Portuguese metallurgical industry - Rodrigues, Catarina (2024)
This research seeks to understand whether employer branding (EB) and internal marketing (IM) are fundamental to the challenge of attracting and retaining talent and how these strategies can help companies to overcome the difficulties related to the talent shortage, from the perspective of a SME Portuguese metallurgical industry.